2020
DOI: 10.1523/jneurosci.1134-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Purpose-Dependent Consequences of Temporal Expectations Serving Perception and Action

Abstract: Temporal expectations enable anticipatory brain states that prepare us for upcoming perception and action. We investigated the purpose-dependent nature and consequences of cued temporal expectations on brain and behaviour in male and female human volunteers, using two matched visual-motor tasks that stressed either response speed or visual accuracy. We show that the consequences of temporal expectations are fundamentally purpose dependent. Temporal expectations predominantly affected response times when visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 70 publications
6
22
0
Order By: Relevance
“…While lateralized power of beta oscillations (15–30 Hz) was sensitive to the type of hazard rate, the effect was weaker and not statistically significant in the alpha band. Related to this, a recent study found that temporal expectations modulate lateralized oscillatory power in a frequency- and modality-specific way ( van Ede et al., 2020 ). It is at present unclear whether and under which circumstances the power of lateralized alpha oscillations signifies the distribution of auditory attention in time.…”
Section: Introductionmentioning
confidence: 72%
“…While lateralized power of beta oscillations (15–30 Hz) was sensitive to the type of hazard rate, the effect was weaker and not statistically significant in the alpha band. Related to this, a recent study found that temporal expectations modulate lateralized oscillatory power in a frequency- and modality-specific way ( van Ede et al., 2020 ). It is at present unclear whether and under which circumstances the power of lateralized alpha oscillations signifies the distribution of auditory attention in time.…”
Section: Introductionmentioning
confidence: 72%
“…The time course of the alpha power response has been shown to exhibit relatively slow modulations with alternating states of higher versus lower alpha power, which align with temporal expectations (e.g. Herbst & Obleser, 2017;Rohenkohl & Nobre, 2011;van Ede et al, 2020;Wilsch et al, 2020), with the presentation rate of sensory stimuli (e.g. Wilson & Foxe, 2020;Wöstmann et al, 2016), and with time-varying goals to attend versus ignore external stimuli (e.g.…”
Section: Functional Specification Requires Anatomical and Temporal Separationmentioning
confidence: 85%
“…These findings implicate the cerebellum in temporal preparation, but are agnostic to whether it has a role in attentional modulation of perceptual systems, in motor preparation, or in both. This is because in speeded detection tasks, reaction time benefits from temporal cues could result from adjustment of perceptual sensitivity and/or of motor preparation 3,[15][16][17] . Given the well documented role of the cerebellum in precisely timed movement 18,19 , the impairments we observed in the CD group may merely reflect a novel manifestation of the cerebellar role in the temporal control of motor preparation 20 .…”
Section: Introductionmentioning
confidence: 99%